Self Regulated Learning as a Psychological Mechanism Linking Growth Mindset and Academic Grit - Jahara, Aini; Hardjo, Suryani; Dewi, Salamiah Sari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The transformation of digital learning requires students to develop academic resilience, reflected in sustained interest and perseverance in pursuing long-term goals. Academic grit is influenced by beliefs about the malleability of one’s abilities (growth mindset) as well as the capacity to manage learning processes independently (self-regulated learning). This study aims to examine the effect of growth mindset on academic grit through the mediating role of self regulated learning among senior high school students MAN 1 Medan . This research employed a quantitative explanatory approach with a survey design involving 374 students selected through random sampling. The research instruments met the criteria for validity and reliability (composite reliability > 0.70). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Model evaluation indicated that the R² value for academic grit was in the moderate category and that Q² > 0, demonstrating adequate predictive relevance. The findings revealed that growth mindset had a positive and significant effect on academic grit (β = 0.393; p < 0.001) and on self regulated learning (β = 0.551; p < 0.001). Self regulated learning also had a positive and significant effect on academic grit (β = 0.294; p < 0.001) and partially mediated the relationship between growth mindset and academic grit (indirect β = 0.162; p < 0.001). These results confirm that growth mindset serves as the primary predictor of students’ academic resilience, while self regulated learning strengthens the underlying psychological mechanism.Transformasi pembelajaran digital menuntut siswa memiliki ketahanan akademik yang tercermin dalam konsistensi minat dan ketekunan mencapai tujuan jangka panjang. Academic grit dipengaruhi oleh keyakinan terhadap kemampuan yang dapat berkembang (growth mindset) serta kemampuan mengelola proses belajar secara mandiri (self-regulated learning). Penelitian ini bertujuan menguji pengaruh growth mindset terhadap academic grit melalui peran mediasi self regulated learning pada siswa MAN 1 Medan . Penelitian menggunakan pendekatan kuantitatif eksplanatori dengan desain survei terhadap 374 siswa yang dipilih melalui random sampling. Instrumen memenuhi kriteria validitas dan reliabilitas (composite reliability > 0,70). Analisis data dilakukan menggunakan SEM-PLS. Evaluasi model menunjukkan nilai R² academic grit berada pada kategori moderat dan Q² > 0, yang menandakan relevansi prediktif yang baik. Hasil penelitian menunjukkan bahwa growth mindset berpengaruh positif dan signifikan terhadap academic grit (β = 0,393; p < 0,001) dan terhadap self regulated learning (β = 0,551; p < 0,001). Self regulated learning juga berpengaruh positif dan signifikan terhadap academic grit (β = 0,294; p < 0,001) serta memediasi secara parsial hubungan antara growth mindset dan academic grit (β tidak langsung = 0,162; p < 0,001). Temuan ini menegaskan bahwa growth mindset merupakan prediktor utama ketahanan akademik siswa, dengan self regulated learning sebagai penguat mekanisme psikologisnya.